Perancangan Komunikasi Visual Makam bung Karno Berbasis Sejarah Untuk Menjadi Tempat Tujuan Wisata Kota Blitar - Pradhika, Moch Romawan; Bahruddin, Muh; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Blitar is one of the cities in Indonesia, which has the potential for historical tourism. One of them is the Tomb of Bung Karno. Bung Karno Tomb is the tomb of Indonesia proclaimed the theme of education, because there are quite a large library. At the Tomb of Bung Karno complex consists of three places, the first Library of Bung Karno, Bung Karno Tomb second and the third is the Museum of Bung Karno. The problem Makam Bung Karno does not yet have a logo and promotional media when a logo is an image or symbol element essential identity. The purpose of this study was to design a logo and supporting media-based promotions Makam Bung Karno Bung Karno Sejarah.Makam located in the northern city of Blitar, East Java. Precisely located at Jalan Ir. Sukarno, who was in the District Bendogerit Sananwetan. Bung Karno Library adjacent to the Tomb of Bung Karno provide archives and books that depict the history of the struggle of Bung Karno in the pursuit of Indonesian independence. The Library Development aims to increase tourist attraction Tomb of Bung Karno who acted as one of the attractions of history and religion mainstay in the city of Blitar.Keywords: Tomb of Bung Karno, Visual Communication, History, Travel Kota Blitar, Superior.